2006
DOI: 10.1196/annals.1372.033
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Ameliorates Some Biochemical Parameters in Normal and Diabetic Rats

Abstract: Diabetes is associated with hyperglycemia, one of the most important causes of oxidative stress. Endogenous antioxidants are able to destroy the reactive species and create a balance between antioxidant and free radicals. In diabetes, the oxidative stress is increased due to the deficiency in the antioxidant defense. The intake of antioxidants, such as vitamin E, may reduce the oxidative stress associated with diabetes and hence help to restore the antioxidant defense system. The aim of this article was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Intake of antioxidants, such as vitamin E 24 and α-lipoic acid 25 , which functions as a cofactor in multi-enzyme complexes, have been successfully used to reverse the oxidative stress produced by hyperglycemia in human diabetics and in STZ-induced diabetic animal models. Oral treatment of α-lipoic acid (600 mg per day orally for five weeks) improved neuropathic deficits in diabetic patients with distal symmetric polyneuropathy in a recent clinical trial 25 .…”
Section: Pathogenesismentioning
confidence: 99%
“…Intake of antioxidants, such as vitamin E 24 and α-lipoic acid 25 , which functions as a cofactor in multi-enzyme complexes, have been successfully used to reverse the oxidative stress produced by hyperglycemia in human diabetics and in STZ-induced diabetic animal models. Oral treatment of α-lipoic acid (600 mg per day orally for five weeks) improved neuropathic deficits in diabetic patients with distal symmetric polyneuropathy in a recent clinical trial 25 .…”
Section: Pathogenesismentioning
confidence: 99%
“…The pathological changes in liver of alloxan and streptozotocin induced diabetic animals have been previously reported Herrman & Sandhu et al 50,51 Zhang et al 52 reported an increased serum levels of ALT and AST in diabetic rats. Ohaeri, 53 Al-shamshi et al; 54 Fadillioglu et al 55 also reported an increased serum ALT and AST in diabetes patients than in the general population (Figures 1-4). The results of this study however disagree with the results of Jianpu et al 56 who reported that serum ALT and AST levels in diabetic rabbits were within normal ranges and Gidado et al 21 who reported insignificant changes in serum levels of ALT and AST in diabetic rats.…”
Section: Discussionmentioning
confidence: 90%
“…Studies using supplements of enzymatic endogenous antioxidants such as SOD, CAT, and glutathione peroxidase to treat diseases have been reported [16,17]. Many studies have also been performed looking into the ability of non-enzymatic antioxidants (vitamin C, E, tocopherol) to either prevent and/or cure a large variety of diseases, including diabetes mellitus [18,19]. These reports showed that vitamin C and E have beneficial effects on the outcome of diseases [18][19][20][21][22][23].…”
Section: Nociceptin Oxidative Stress and Diabetes Mellitusmentioning
confidence: 99%